Effect of esketamine on postoperative depressive symptoms in patients undergoing thoracoscopic lung cancer surgery: A randomized controlled trial - Gan, Shu-lin; Long, Yu-qin; Wang, Qin-yun; Feng, Chang-dong; Lai, Chen-xu; Liu, Chun-tong; Ding, Yun-ying; Liu, Hong; Peng, Ke; Ji, Fu-hai (Frontiers in Psychiatry, 2023)
Background Depressive symptoms are common among patients with lung cancer. We aimed to assess the effects of esketamine on postoperative depressive symptoms after thoracoscopic lung cancer surgery. Methods In this randomized, double-blind, placebo-controlled trial, 156 patients undergoing thoracoscopic lung cancer surgery were randomly allocated in a 1:1 ratio to receive intravenous esketamine (intraoperatively and in patient-controlled analgesia until 48 h postoperatively) or normal saline placebo. The primary outcome was the proportion of patients with depressive symptoms at 1 month postoperatively, assessed using the Beck Depression Inventory-II (BDI-II). Secondary outcomes included depressive symptoms at 48 h postoperatively, hospital discharge and 3 months postoperatively, BDI-II scores, anxious symptoms, Beck Anxiety Inventory scores, Quality of Recovery-15 (QoR-15) scores, and 1- and 3-month mortality. Main results A total of 151 patients (75 in the esketamine group and 76 in the normal saline group) completed the 1-month follow-up. The esketamine group had a significantly lower incidence of depressive symptoms at 1 month compared to the normal saline group (1.3% vs. 11.8%; risk difference = −10.5, 95%CI = −19.6% to −0.49%; p = 0.018). After excluding patients without lung cancer diagnosis, the incidence of depressive symptoms was also lower in the esketamine group (1.4% vs. 12.2%; risk difference = −10.8, 95%CI = −20.2% to −0.52%; p = 0.018). The secondary outcomes were similar between groups, except that the esketamine group had higher QoR-15 scores at 1 month postoperatively (median difference = 2; 95%CI = 0 to 5; p = 0.048). The independent risk factors for depressive symptoms were hypertension (odds ratio = 6.75, 95%CI = 1.13 to 40.31; p = 0.036) and preoperative anxious symptoms (odds ratio = 23.83, 95%CI = 3.41 to 166.33; p = 0.001). Conclusion Perioperative administration of esketamine reduced the incidence of depressive symptoms at 1 month after thoracoscopic lung cancer surgery. History of hypertension and preoperative anxious symptoms were independent risk factors for depressive symptoms. Clinical trial registration: Chinese Clinical Trial Registry http://www.chictr.org.cn, Identifier (ChiCTR2100046194).